(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
We aimed to study the antioxidant and anti-inflammatory activity of extracts from Teucrium polium leaves on BV-2 microglial cell line models, particularly wild-type (Wt) and Acyl-CoA oxidase 1 deficient (Acox1−/−) cell line models, which are useful for examining specific neurodegenerative disorders. The analysis showed that the extract contains a high number of flavonoids and phenolic compounds. The MTT assay showed that the concentration of 0.125 mg/mL of T. polium extract was the highest that exhibited no toxicity. The chemical-based tests showed that the extract has high antioxidant activity. The high antioxidant potential was further verified through research using BV-2 microglial cell line models. Furthermore, the extract was detected to affect the activity of the key antioxidant enzyme catalase in both Wt and Acox1−/− BV-2 microglial cell lines. Additionally, the extract affected LPS-induced nitric oxide generation, as well as the expression of relevant genes in Wt and Acox1−/− BV-2 microglial cells, such as Cat, iNos, Il-1β, Tnf-α, and Abcd1. These results suggest that T. polium extract exerts regulatory and anti-inflammatory effects by modulating the expression levels of these genes.